Musculoskeletal care pathways for adults with hip and knee pain at the interface between primary and secondary care: protocol for a systematic review. Issue 1 (December 2016) - Button, Kate; Morgan, Fiona; Hodgson, Helen; Weightman, Alison; Jones, Steve
Abstract Background Musculoskeletal (MSK) conditions are the most frequently reported chronic conditions and one of the biggest causes of disability in the UK. Given the ageing population and the impact of these problems, the demand for MSK treatment will rise. Despite reduced waiting times, MSK pathways have remained variable and inconsistent and need to be improved to meet patient needs. The aim of this systematic review is to understand the evidence for the effectiveness of current models of service delivery and care pathways for adult hip/knee pain patients accessing secondary care for specialist opinions. Methods MEDLINE, MEDLINE In-Process, CINAHL, Embase, PEDro, PubMed, Web of Science, Cochrane Central and HMIC databases will be searched without language restrictions for papers published from 1990 onward. Websites will be reviewed for grey literature including care pathways, policy documents and unpublished MSK research. Additionally, reference lists will be checked and citations tracked for included studies. Discussion The following evidence will be included: research considering care pathways at the intersection between primary and secondary care for adults with hip and/or knee pain in countries with an established clinical pathway. Studies considering generalised inflammatory arthropathy and post-surgical care pathways will be excluded. Screening for included data will be conducted independently by two reviewers. After benchmarking, quality assessment and data extraction will be conducted by one reviewer and checked by a second. A mixed method analysis will be conducted. This systematic review will be used as part of a programme of research to identify best practice for MSK hip and knee pain care pathways. It will provide recommendations for pathway re-design to meet patient needs and ensure efficient streamlining of the patient journey. The review will combine a wide range of information sources including patient and clinician opinion, clinical guidelines, health service delivery research and stakeholder requirements. This should result in a pathway that provides better patient experience and outcomes, whilst meeting the demands placed on the NHS for high-quality evidence-based interventions with efficient use of resources. Systematic review registration PROSPEROCRD42016035510